2016
DOI: 10.1061/(asce)co.1943-7862.0001044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cooperation during Project Delivery: Empirical Study on the Hydropower Industry in Southwest China

Abstract: Previous studies agree that cooperation among participants is critical to successfully deliver projects; however, little research has quantitatively illustrated how participants benefit from cooperation. Based on partnering and cooperative game theories, the Degree of Willingness to Cooperate (DWC) model has been used in this study to reflect the interactions among participants through dynamic simulation. With the support of data collected from a field survey, the outcomes of DWC model simulation have been tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Game theory has been used to examine the conflict and cooperation between rational decision makers [32,33]. Game theory provides a useful approach to study the conceptual aspects of construction projects [34][35][36][37], and provides useful insights into the way that the participants utilize the resources under different situations. The grounded model can be used to simulate and analyze the effects of cooperative behavior on the stakeholders' net benefits, the overall project benefits, and the benefits' allocation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Game theory has been used to examine the conflict and cooperation between rational decision makers [32,33]. Game theory provides a useful approach to study the conceptual aspects of construction projects [34][35][36][37], and provides useful insights into the way that the participants utilize the resources under different situations. The grounded model can be used to simulate and analyze the effects of cooperative behavior on the stakeholders' net benefits, the overall project benefits, and the benefits' allocation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The environment management of hydropower development includes planning, organization, implementation, and control [41]. By studying the Himalaya Dams in India, Grumbine and Pandit demonstrated that the improvement of planning and implementation of environmental protection is crucial to the development of hydropower projects [42].…”
Section: Literature Review On Environment Management Of Hydropower Developmentmentioning
confidence: 99%
“…To tackle the increase of environment-related disputes, project participants should jointly establish environment management systems and processes and cooperatively solve environmental problems. This would allow participants to clearly understand their responsibilities and have the motivations and necessary resources to achieve environmental protection objectives [41,47,48]. Sternberg indicated that hydropower development should also make environmental technical improvements to minimize environmental influence [49].…”
Section: Literature Review On Environment Management Of Hydropower Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Naderpajouh et al (2014) used it in risk management between developer and opposition in infrastructure developments. Also, game theory has been used in the payment problems (Wu et al 2011), renewal of construction objects (Antuchevičiene et al 2006), cooperation during project delivery (He et al 2016), and post-disaster management (Eid et al 2015). Even some researchers have used game theory in studying the delayed projects (Castro et al2007;Estévez-Fernández 2012).…”
Section: Dispute Resolution Methodsmentioning
confidence: 99%